Pendekatan Sosiologis dalam Studi Agama; Signifikansinya Terhadap Kemajuan Peradaban Islam - Siregar, Anwar Habibi (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
AbstractThe various challenges faced by humanity today highlight the need to view religion as a holistic source of solutions. Beyond merely a symbol of virtue, religion also provides an effective conceptual framework for addressing the myriad complex issues we encounter. In this context, there is a call to transcend the understanding of religion limited to normative theological frameworks and to incorporate alternative approaches, including sociological ones, capable of providing practical answers to emerging challenges. The presence of sociological approaches becomes increasingly urgent as they offer a more open perspective on religious teachings relevant to the social contexts we face. Thus, these approaches open the door to a deeper understanding of religion, not only as a spiritual guide but also as an instrument derived to achieve broader social goals.Keywords: Role of religion, theological approach, sociological approach, social complexity